EVOLUTION OF PADDY ZAKAT MANAGEMENT IN THE STATE OF KEDAH - Rabitah Harun; Nurul Hayani Abd Rahman; Mazura Mat Din; Shaifizat Mansor; Khairul Adilah Ahmad, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The fundamental tenet of Islam's social structure is the mandatory almsgiving, or zakat. The challenges and suffering of the impoverished are supposed to be lessened with the proper and sufficient execution of zakat institutions and management. Kedah is known as the largest paddy cultivator in Malaysia and has a long history in zakat management by the Kedah State Zakat Board (LZNK) back in 1935. This paper intends to examine the evolution and management of paddy zakat, starting from its existing management, technological integration, and future orientation. The introductory reviews are based on previous and relevant research on the management of paddy zakat collection and distribution in the state of Kedah, with a focus on the shift from traditional methods to the integration of digital technologies. Apart from that, a few prospects have been investigated to improve Kedah's paddy zakat management, such as special educational awareness programs, agriculture institution collaboration, and special projects for income generation. Information and data searches were collected via library searches and searching databases. With an eye on maximising social impact and guaranteeing adherence to Islamic law, the modernisation of zakat institutions throughout Malaysia is reflected in the development of paddy zakat management in Kedah.